Subsolidus phase equilibria of the CuO – SrO – ZnO pseudoternary system in air at 900 °C - J.-C. Grivel (Chimica Techno Acta)
The subsolidus phase equilibria of the CuO – SrO – ZnO system were determined at 900 °C in air. The pseudoternary section does not contain ternary oxide phases but is made of 5 three-phase regions and 2 narrow two-phase regions linked to a Sr14Cu24-xZnxO41-y solid solution. The maximum solubility of Zn in this phase is limited to x ≈ 0.1, but this low doping level results in a significant decrease of the electrical resistivity by about one order of magnitude compared to the undoped compound. The other binary oxide phases SrZnO2,Sr2CuO3, and SrCuO2 do not form solid solutions extending into the ternary system. SrZnO2 was found to decompose upon contact with ambient air.